A nutrigenomics approach to study the effects of ω-3 fatty acids in laying hens under physiological stress - Berenjian, Atefeh; Bakhtiarizadeh, Mohammad Reza; Mohammadi-Sangcheshmeh, Abdollah; Sharifi, Seyed Davood (Frontiers in Physiology, 2023)
Supplement of ω-3 fatty acids can decrease the harmful effects of stress. However, the potential molecular mechanisms that are modulated by dietary ω-3 fatty acids in laying hens under stress remain unknown. Hence, RNA-sequencing (RNA-Seq) technology was used to gain new insights into different gene expression profiles and potential pathways involved in response to stress in the liver of 35-week-old Lohmann LSL-Lite laying hens supplemented with ω-3. Three groups including control (non-stress), stress, and stress_ω-3 fatty acids (three layers per each group) were applied. A total of 1,321 genes were detected as differentially expressed genes (DEGs), of which 701, 1,049, and 86 DEGs belonged to stress vs control, stress_ω-3 vs control, and stress vs stress_ω-3 pairwise comparisons, respectively. Gene ontology and KEGG pathway analysis indicated that the DEGs were enriched in particular regulation of steroid and cholesterol biosynthetic process, fatty acid degradation, AMPK signaling pathway, fatty acid biosynthesis, and immune response. Our data represented a promising approach regarding the importance of ω-3 as anxiolytic and anti-stress. In this context, UNC13B and ADRA1B genes were down-regulated in the stress_ω-3 group compared to the stress group, which are associated with decreased activity of glutamatergic stimulatory neurons and probably play important role in facilitating the response to stress. This study extends the current understanding of the liver transcriptome response to physiological stress, and provides new insights into the molecular responses to stress in laying hens fed a diet supplemented with ω-3 fatty acids.